Investing in People : Sustaining Communities through Improved Business Practice - International Finance Corporation (Washington, DC: World Bank, 2013)
The private sector, as an increasingly significant catalyst for positive change, and as an innovative challenger, is faced with demonstrating responsibility, and accountability in the development process. The fast evolution in communications means that companies' environmental, and social performance are greatly scrutinized by the widening stakeholder audience, thus, understanding the boundaries of private sector corporate responsibility is evolving at a rapid pace. As a result, new innovative models of assurance, accountability, and partnership are emerging, which will seemingly - and hopefully - lay the foundation for sound business performance. In response, the International Finance Corporation (IFC) has prepared this Community Development Resource Guide, which builds on concrete examples of corporations, and projects where complex environmental, and social impacts have been dealt with innovatively, and successfully. Key principles for community development programs, define the framework of this document, i.e., the need to engage in effective community consultation, to form the basis for building trust, and further manage expectations, by defining roles, and responsibilities, developing appropriate capacities, and mobilizing core competencies to set measurable goals, and monitor business best practices.